Understanding Girl with Balloon: A metaphorical and semiotic analysis of Banksy's Street Work - Margaretha, Regyna; Hartono, Hendri; Afrilia, Nur Sitha (Priviet Social Sciences Journal, 2025)
Street art has become a powerful medium for conveying social and political messages. Banksy, an anonymous street artist, creates meaningful works, one of which is the Girl with Balloon. This study aims to analyze the metaphorical meaning of the work using a semiotic approach. This approach is based on the theory of signs by Ferdinand de Saussure and Charles Sanders Peirce to identify how visual signs in the work form deeper meaning. The analysis shows that the elements in Girl with Balloon convey messages about loss, hope, and the future. The heart-shaped balloon symbolizes love and dreams, while the little girl who reaches for it represents human efforts to achieve hopes that often feel far away. Thus, this work is not just visual art but also a social critique that can arouse emotions and reflections in society.